The Influence of Work Competence, Mutation, and Promotion on Employee’s Performance at Finishing Department of CV Laksana Karoseri Ungaran - Yunita Dwi Lestari; Rustono - Rustono; Eva - Purnamasari (Politeknik Negeri Semarang, 2021)
This study aimed to analyze the effect of work competence, mutation, and promotion on the performance of finishing employees at CV Laksana Karoseri Ungaran. The population in this study were all 72 employees of the finishing department, and the sample was 61 employees who were selected using nonprobability sampling technique with purposive sampling method. The data analysis model used in this study is a multiple linear regression analysis model and the analysis technique used the f test and partial test (t test) with the SPSS 24 program. The results of hypothesis testing indicate that work competence and promotion has a significant positive effects on employee’s performance, while mutation variable has no significant effect on employee performance. The results of the f test show that together the variables of work competence, mutation, and promotion have a significant positive effects on the employee’s performance in the finishing department of CV Laksana Karoseri Ungaran